Gender and informality at work – theoretical provocations: an introduction to the special issue on gender and informality. (3rd April 2018) - Coles, Amanda; Macdonald, Fiona; Delaney, Annie
ABSTRACT: This special issue examines the interaction of gender with informal work, processes of informalisation and experiences of informality as a defining feature of work under contemporary capitalism. The articles interrogate the interactions between the experiential, discursive and structural dimensions of informality as they emerge in relation to the social construction of gender relations. These analyses present a comprehensive survey of the 'continuum of practices' which constitute informality, and draws attention to the urgency of understanding the ways in which codified and social practices normalise, formalise and conceal the gendered dimensions of informality at work.